2013
DOI: 10.1111/ssqu.12066
|View full text |Cite
|
Sign up to set email alerts
|

Expectations in Mass Elections: Back to the Future?

Abstract: Objectives This article examines whether voters look to the past or the future when forming their perceptions of the parties’ chances of winning. Methods We use OLS regression models to analyze panel survey data from the districts where the incumbent was defeated in the 2011 provincial election in Ontario (Canada). Results We find that voters’ expectations in the districts are mainly affected by the results of the upcoming election and not by the outcome of the previous election. We also find that expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…While many studies have focused on perceptions of economic conditions, we should note that scholars have also examined whether people accurately assess other conditions related to political life, including perceived levels of political competition and projections of election outcomes. For instance, some scholars (Guinjoan et al 2014; McDonald and Tolbert 2012) have found that perceived levels of political competition correspond to actual levels of competition in congressional elections, and others have found that, in aggregate, survey respondents do a pretty good job predicting actual election outcomes (Holbrook 2010; Lewis-Beck and Skalaban 1989).…”
Section: Previous Research and Expectationsmentioning
confidence: 99%
“…While many studies have focused on perceptions of economic conditions, we should note that scholars have also examined whether people accurately assess other conditions related to political life, including perceived levels of political competition and projections of election outcomes. For instance, some scholars (Guinjoan et al 2014; McDonald and Tolbert 2012) have found that perceived levels of political competition correspond to actual levels of competition in congressional elections, and others have found that, in aggregate, survey respondents do a pretty good job predicting actual election outcomes (Holbrook 2010; Lewis-Beck and Skalaban 1989).…”
Section: Previous Research and Expectationsmentioning
confidence: 99%
“…However, even though this presents us with limitations concerning our analyses, we also believe that district viability was much less uncertain than government viability during the 2014 campaign, and that our objective measure of the former reflects voter's subjective evaluations. Some studies show that voters manage to update their expectations regarding the chances of the parties in their district on the basis of the polls released during the campaign (Guinjoan et al 2014; Blais and Bodet 2006). However, we also replicated our analyses with the results of previous elections (2010 for federal, and 2009 for regional elections) in order to check the robustness of our results.…”
Section: Table 1 Parties Included In the Study And Description Of Thmentioning
confidence: 76%
“…However, these models depart from the central assumption of forward-looking utility maximization in the calculus. Moreover, the main assumption of these models-that the turnout decision is based on perceptions of positive or negative outcomes associated with past actions-generally fails to correspond with empirical evidence regarding the motivating factors of turnout (Dowding 2005, 451;Guinjoan et al 2014).…”
Section: The Paradox Of Voter Turnoutmentioning
confidence: 97%